Metataxonomic insights into lactic acid bacteria diversity in artisanal coalho cheese from the Caatinga biome - Ruana Célia Gomes De Morais Costa Rodrigues; Emmanuella de Oliveira Moura Araújo; Samira Teixeira da Silva; Gustavo Felipe Correia Sales; Danielle Cavalcanti Sales; Mauricio Tolstoi do Santos Ferreira; Cláudio Vaz Di Mambro Ribeiro; Luis Medeiros de Lucena; Claudio Cipolat-Gotet; Maria Taciana Holanda Cavalcanti; Adriano Henrique do Nascimento Rangel (PLoS ONE, 2026)
Artisanal raw-milk cheeses are complex microbial ecosystems that reflect local environments through spontaneous fermentation driven by lactic acid bacteria (LAB), processing practices, and the quality of raw materials. The Caatinga biome, a unique semi-arid ecosystem in Northeastern Brazil, presents distinctive environmental and cultural conditions which can significantly influence the microbial composition of traditional dairy products. This study aimed This study aimed to characterize the bacterial community, with emphasis on lactic acid bacteria (LAB), in artisanal Coalho cheese produced in the Seridó region using 16S rRNA gene-based metataxonomic analysis. A total of 32 cheese samples from eight municipalities were collected and homogenized into a representative composite sample. DNA was extracted and the V3–V4 region of the 16S rRNA gene was sequenced using the Illumina MiSeq platform (paired-end 2 × 300 bp). The microbial community was dominated by LAB, particularly Enterococcus (~25%), followed by Lactococcus, Streptococcus, and Leuconostoc. The predominance of these genera reflects the spontaneous fermentation process typical of artisanal raw-milk cheeses and highlights their role in acidification, flavor development, and microbial stability. The microbial community was dominated by LAB, particularly Enterococcus (~25%), followed by Lactococcus , Streptococcus , and Leuconostoc . The predominance of these genera reflects the spontaneous fermentation process typical of artisanal raw-milk cheeses and highlights their role in acidification, flavor development, and microbial stability. This study provides the first metataxonomic insight into the microbiota of artisanal Coalho cheese produced in the Seridó region of the state of Rio Grande do Norte, highlighting its microbial richness and biotechnological potential, and supporting its valorisation and the sustainable development of regional cheese production. Although the use of pooled samples limits the assessment of intra-regional variability, the results establish a foundational understanding of the microbial community structure and support future investigations focused on functional characterization, food safety, and process standardization.